The Adoption of Agriculture Technology in Small-Scale Farming in The Adumasa Community in Ghana - Antwi, Daniel Kwesi; Gyamera, Ebnezer; Abdulshakur, Mahmud (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to identify socio-economic and institutional factors influencing the adoption of agricultural technologies by small-scale farmers in Adumasa. The study explores the types of technologies used and the factors that determine their adoption decisions, considering their benefits and drawbacks. Methodology: This study used a qualitative approach with a sample of 15 farmers from the Adumasa community (10 adopters and 5 non-adopters), paying attention to gender equality (8 males and 7 females). Data were collected through direct/telephone interviews, field observations, and document analysis, using interview guides and observation notes as instruments. Data analysis was carried out thematically with the help of Atlas.ti to identify patterns of factors influencing the adoption of agricultural technology. Main Findings: The results of the study showed that the application of agricultural technology increased agricultural productivity by up to 25% compared to conventional methods and improved the economic welfare of farmers through increased income and work efficiency. Novelty/Originality of this study: The novelty of this study lies in the comprehensive analysis of the impact of agricultural technology on the socio-economic aspects of farmers. This study contributes to the formulation of technology-based agricultural policies to improve food security and farmer welfare.